A atual perspectiva dos grupos de direito no Brasil: um estudo empírico sobre os grupos de direito no estado de São Paulo - Cury, Felipe Augusto (2016)
The purpose of this research is to identify the contract groups established in São Paulo state in order to understand and analyze the reasons why such groups were established, through the analyzes of their conventions. The importance of such research it to contribute with the reflection regarding the subject, because of the inexistence of an empirical approach concerning the existing contract groups. Frequently, scholars sentences the legal discipline enclosed in Chapter XXI of the Brazilian Corporation Law as a 'dead letter', without bringing empirical data that supports such valoration. However, in an exploratory research, it is possible to identify the existence of fifteen (15) contract groups established in São Paulo state, which indicates that such discipline is not completely unused. So, one question is presented: why such contract groups exists, regardless of their apparent failure? As a result of the research should be highlighted: (i) as its form, conventions, mostly, although the Law 6,404 / 76, article 269 and items, dispose of its required elements, it appears that there is no effective implementation of some of these elements, provided they specify in general the name, purpose, the award of the administrative body and who will be the parent company and who is (are) to (s) controlled (s); (ii) as to their content, conventions seek to legitimize the subordination of interests, through the action of the administrative body, which leads the business of the group for the benefit of societies. This is accomplished without any possible conflict of interest, since the stock ownership of the parent company, subsidiaries and management body are concentrated in the hands of the same shareholders; (iii) the absence of subordination of the interests of societies shows that the right groups matter to its constitution to achieve the main objective, which is not always explained clearly by the conventions; (iv) the typical profile of the groups is the group of corporate type of limited liability companies, whose typical profile which control is exercised or 1 partner or two partners with similar interests, and also exercises (m) the management of both companies as a group.